Implementasi Pembelajaran Al-Qur’an Berbasis Digital Dalam Meningkatkan Literasi Dan Motivasi Belajar Siswa MTs Darussalam Banjar Negeri Kecamatan Natar Lampung Selatan - Sutarmi; Siti Raudhatul Jannah; Agus Setiawan (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2025)
Implementation of Digital-Based Tilawatil Al-Qur'an Learning is a process of applying technology in Tilawatil Al-Qur'an teaching and learning activities which aims to improve the effectiveness, understanding, and motivation of students in reading the Qur'an properly and correctly, in accordance with the rules of tajwid and the rhythm of the tilawah. This study aims to describe the implementation of digital-based Tilawatil Al-Qur'an learning using projectors and YouTube videos in improving literacy and student learning motivation at MTs Darussalam Banjar Negeri, Natar District, South Lampung. The background of this study is based on the importance of improving the quality of Tilawatil Al-Qur'an learning so that students are not only able to read the Qur'an properly and correctly, but also have a high enthusiasm for learning. This study uses a Qualitative research method with a case study research type (field research). By using data collection techniques in the form of observation, interviews and documentation. Data validity testing uses triangulation. And the data analysis techniques are data reduction, data presentation, conclusions. The results of the study indicate that the implementation of digital media in learning Tilawatil Al-Qur'an has a positive impact on students' literacy skills, especially in understanding the laws of tajwid, makhraj, and rhythm of tilawah. Learning videos from YouTube displayed through a projector make it easier for students to imitate examples of professional qari readings, thereby accelerating the learning process and increasing students' self-confidence. In addition, students' learning motivation has increased significantly, marked by high enthusiasm, active participation, and perseverance in completing tilawah tasks. Based on these findings, the use of digital media in learning Tilawatil Al-Qur'an is highly recommended to be implemented sustainably in order to improve the quality of Islamic religious education at the madrasah level. This study provides a significant contribution in the development of Tilawatil Al-Qur'an learning methods in the madrasah environment, especially in the use of digital technology as a learning medium. Practically, the results of this study can be used as a reference for educators in designing more interactive and interesting learning strategies, in order to improve Al-Qur'an literacy and student learning motivation. Keywords: Learning Implementation; digital media; student learning motivation.